Gender-stratified 9-month comparison of paliperidone extended-release tablets and paliperidone palmitate injection in schizophrenia - Lan, Zheng; Long, Zhiguang; Jiang, Haiyan; Huang, Cuishan; Huang, Wei (Frontiers in Psychiatry, 2025)
BackgroundGender differences in antipsychotic efficacy for schizophrenia (SCZ) remain understudied despite evidence of sex-dependent pharmacokinetic, neurobiological, and social factors influencing outcomes. This trial compared 9 - month efficacy and tolerability of paliperidone palmitate injection 1-monthly (PP1M) versus extended-release tablets in male and female patients with SCZ, with a focus on gender-stratified results.MethodsThis randomized, open-label study enrolled 118 adult patients (61 males, 57 females) diagnosed with SCZ. Participants were randomized (1:1) to receive either paliperidone extended-release (ER) tablets (titrated 3–12 mg/day) or PP1M (3–9 mg monthly). Efficacy was assessed via PANSS total scores and CGI-S severity ratings at 3, 6, and 9 months. Safety was evaluated using the TESS scale.ResultsGender-stratified analysis revealed superior long-term efficacy for males treated with paliperidone palmitate injection. Males treated with PP1M demonstrated significantly greater reductions in PANSS scores (mean difference at 9 months: -7.44; p < 0.05) and CGI-S severity compared to ER therapy. Females showed no statistically significant differences between formulations at any time point, with overlapping confidence intervals (e.g., PANSS mean difference at 9 months: +3.16; p > 0.05). Both groups exhibited comparable tolerability, with minimal adverse events.ConclusionGender-informed treatment strategies are critical in SCZ management. PP1M appears advantageous for males seeking long-term symptom stabilization, while treatment selection for females may prioritize lifestyle factors. These findings underscore the need for sex-stratified analysis in antipsychotic trials and the importance of tailored interventions to address sex-based disparities in psychiatric care.